INTENTION TO INVEST IN SHARIA CAPITAL MARKET USING THEORY OF PLANNED BEHAVIOR (TPB) - Sulastri, Tuti (I-Economics, 2023)
As a country with a majority Muslim population and a beneficiary of the demographic bonus phenomenon, Indonesia certainly offers good opportunities for capital market growth. Investment interest is a guideline of assets allocated to investment options for future profits. The purpose of this study is to measure and analyze investments attitudes, subjective norms, perceptions of behavioral control over investment interest with financial literacy as a moderating variable. This research is a type of quantitative research. The population in this study are people who have savings to invest. The method of determining the sample is target sampling. The sample for this study consisted of his 280 respondents. The data in this study are based on primary data. This study uses the Partial Least Squares (PLS) analysis tool. The results of this study show that investment attitudes have a direct and significant effect on investment returns, while subjective norms have a direct and significant effect on investment returns. Perceived behavioral control has a direct and significant impact on investment returns. Financial literacy mitigates the impact of subjective norms and perceived behavioral controls on investment returns in a positive and important way. On the other hand, financial literacy does not soften investment attitudes toward investees.Keywords: Theory of Planned Behavior, Financial Literacy , Islamic Investment Interest